Neglected Bilateral Posterior Shoulder Fracture Dislocation in an Uncontrolled Seizure patient - Amir, Moaath A. (Pak J Med Sci, 2015)
Posterior dislocation of the shoulder is a rare injury that occurs secondary to trauma and seizures. Diagnosis is often missed and treatment is challenging. Neglected posterior dislocation is associated with Hill-Sachs lesion which leads to locking of dislocation. Correct diagnosis is achieved by history taking, a physical examination and appropriate imaging. In neglected shoulder dislocation with uncontrolled seizure and humeral head defects of up to 45% the McLaughlin procedure shows excellent results at follow-up.